The Influence Of Aerobic Endurance, Hand Eye Coordination And Student Learning Discipline On The Basic Volleyball Technique Skills Of Students Of Smp Negeri 2 Lintau Buo Utara, Tanah Datar Regency - Yona Evasari; Kamal Firdaus; Syafruddin Syafruddin; Hastria Efendi (Badan Penerbit STIEPARI Press, 2023)
The purpose of this study was to see the effect of aerobic endurance, hand eye coordination, and learning discipline on basic volleyball skill items for SMP N 2 North Lintau Buo. This type of research is path analysis (fat analysis) with the variables of aerobic endurance, eye-hand coordination and learning discipline. The population of this study were 20 grade VIII students of SMP N 2 Lintau Buo Utara. The sampling technique in this study was a purposive sampling technique, so that 20 students were randomly selected as the sample at SMP N 2 Lintau Buo Utara. The grouping of samples is random. Data collection was carried out by testing basic volleyball skills, namely passing over, under, serve and serve over. The data was then analyzed by t-test. The results obtained in this study were: 1) There was an effect of aerobic endurance on basic volleyball skill items for students at SMP N 2 Lintau Buo Utara, as evidenced by the average increase in each item of basic skills, namely: upper passing skills (1.5), passing skills underhand pass (1.7), overhand skill (-1.02), and underhand skill (1.9); 2) There is an effect of hand eye coordination on the basic volleyball technique skills of SMP N 2 Lintau Buo Utara, as evidenced by the average results of an increase in each item of basic skills, namely: bag passing skills (2.2), bottom pass skills (2.3), service skills under (-1.47), and over serve skills (3.2) ; 3) There is an influence of learning discipline on the basic volleyball skills of students of SMP N 2 Lintau Buo Utara, as evidenced by the results of the tcount for each item of basic skills, namely: upper passing skills (1.94), lower passing skills (1.82), lower serving skills (2.5) , and top serve skill (2.5) is greater than ttable (1.73).